The imagined island : history, identity, & utopia in Hispaniola - San Miguel, Pedro Luis. (Chapel Hill : University of North Carolina Press, 2005)
National identity in Haiti and the Dominican Republic.
The imagined colony : historical visions of colonial Santo Domingo -- Racial discourse and national identity : Haiti in the Dominican imaginary -- The island of forking paths : Jean Price-Mars and the history of Hispaniola -- Storytelling the nation : memory, history, and narration in Juan Bosch.
"Originally published in Spanish with the title La isla imaginada: historia, identidad y utopía en la Espanõla"--Title page verso.
Translated from the Spanish.
Includes bibliographical references (pages 133-179) and index.
Translated from the Spanish.
Print version record.
Electronic reproduction.
Keywords: Bosch, Juan, -- 1909-2001.; Bosch, Juan, -- 1909-; Bosch, Juan, -- 1909-2001; Dominican Republic -- Historiography; Haiti -- Historiography; Haiti -- Foreign public opinion, Dominican; Intellectuals -- Dominican Republic -- Attitudes; Public opinion -- Dominican Republic; Hispaniola -- Race relations; Politics and literature; Literature and history; Intellectuels -- République dominicaine -- Attitudes; Opinion publique -- République dominicaine; Politique et littérature.; Littérature et histoire; République dominicaine -- Historiographie; Haïti -- Historiographie; Haïti -- Opinion publique dominicaine; Hispaniola -- Relations raciales; HISTORY -- General; Historiography; Intellectuals -- Attitudes; Literature and history; Politics and literature; Public opinion; Race relations; Dominican Republic; Haiti; Hispaniola; Geschichtsschreibung; Hispaniola